Exogenous Hydrogen Sulfide Ameliorates Diabetic Myocardial Fibrosis by Inhibiting Cell Aging Through SIRT6/AMPK Autophagy - Li, Yaling; Liu, Maojun; Song, Xiong; Zheng, Xia; Yi, Jiali; Liu, Da; Wang, Sen; Chu, Chun; Yang, Jun (Frontiers in Pharmacology, 2020)
Stress aging of myocardial cells participates in the mechanism of myocardial fibrosis (MF). Previous studies have shown that hydrogen sulfide (H2S) can improve MF, but its specific internal mechanism is still unclear. In this study, we aim to explore whether H2S can improve myocardial cell aging caused by high glucose and myocardial fibrosis in diabetic rats by activating autophagy through SIRT6/AMPK. We observed that HG(High Glucose:33mM) induced down-regulation of endogenous H2S-producing enzyme CSE protein expression, increased cell senescence, down-regulation of autophagy-related proteins Beclin1, Atg5, Atg16L1, and inhibition of SIRT6/AMPK signaling pathway in H9c2 cardiomyocytes. H2S(NaHS:100μM) could up-regulate CSE protein expression, inhibit cell senescence, activate autophagy and SIRT6/AMPK signaling pathway. On the contrary, addition of CSE inhibitor PAG (dl-propargylglycine：2 mmol/L) could eliminate the above phenomena. In order to further elucidate the relationship between H2S and SIRT6/AMPK signaling pathway, Dorsomorphin dihydrochloride (Dor), an inhibitor of AMPK signaling pathway, was added to the study to observe the reversal of H2S's inhibitory effect on myocardial cell aging. At the same time, streptozotocin (STZ: 40 mg/kg). The myocardial collagen fibers were obviously deposited by immunological method, and the senescent cells were obviously increased by immunofluorescence method. Meanwhile, the expression of CSE protein was down-regulated by immunoblotting method, while SIRT6/AMPK signaling pathway and autophagy were obviously inhibited by H2S intervention ,In conclusion, these findings suggest that exogenous H2S can inhibit myocardial cell senescence and improve diabetic myocardial fibrosis by activating CSE and activating autophagy through SIRT6/AMPK signaling pathway.